Analysis of the value chain in the artisans of the Guano canton through neuro emotions - Pintado Sánchez , Edgar Adrián; Calderón Moran, Edison Vinicio (mktDESCUBRE, 2023)
The objective of this research was to analyze the value chain in the artisans of the Guano canton through neuro emotions. The methodology used was to apply a survey to the artisans of leather, carpets, textile articles and stone of the Guano canton in the year 2022 in two parts, one that addresses the value chain and the other the neuro-emotions and the external population considered as the tourists who they visit Guano. The results of the surveys were tabulated using the Excel program and the results were analyzed through descriptive statistics. The value chain is similar between the artisans who acquire the raw material and sell it in Guano. They supply the town. The prices are homogeneous, they need to improve their sales through the internet. Carpet artisans in their emotions are optimistic and proactive, they do their work with joy and happiness, they are sensitive. In negative emotions it affects them little in their work and they do not have anguish. Leather craftsmen feel love and satisfaction for the created object, and fear does not affect their work. The textile artisans, made up of more women, responded in an intermediate way and were the best at expressing themselves. For stone craftsmen are young men placed lower percentages with votes of more or less or sometimes. Oral expression courses, management of emotions at the time of sale, customer service, management of negative emotions at work are proposed.